Maternal and Paternal Psychological Control as Moderators of the Link between Peer Attitudes and Adolescents’ Risky Sexual Behavior - Oudekerk, Barbara A. (2013)
Maternal and paternal psychological control, peer attitudes, and the interaction of psychological control and peer attitudes at age 13 were examined as predictors of risky sexual behavior before age 16 in a community sample of 181 youth followed from age 13 to 16. Maternal psychological control moderated the link between peer attitudes and sexual behavior. Peer acceptance of early sex predicted greater risky sexual behaviors, but only for teens whose mothers engaged in high levels of psychological control. Paternal psychological control demonstrated the same moderating effect for girls; for boys, however, high levels of paternal control predicted risky sex regardless of peer attitudes. Results are consistent with the theory that peer influences do not replace parental influences with regard to adolescent sexual behavior; rather, parental practices continue to serve an important role either directly forecasting sexual behavior or moderating the link between peer attitudes and sexual behavior.